THE RELATIONSHIP OF EMPLOYEE POTENTIAL, EMPLOYEE COMPETENCE AND WORK MOTIVATION WITH PERFORMANCE OF EMPLOYEES IN THE PUBLIC WORKS AND PEOPLE'S HOUSING DEPARTMENT JAMBI PROVINCE - Ellyta Mona; Ahmad Syukri; Risnita, Risnita (International Journal of Economics and Management Research, 2022)
This study aims to test the hypothesis of the relationship between potential, employee competence and work motivation with employee performance at the Public Works and Public Housing (PUPR) Jambi Province. This research is a quantitative research with survey method. The sampling technique used a probability sampling technique with a sample size of 42 PUPR employees. Hypothesis testing using correlation analysis with a significance level of = 0.05. Data Result This research concludes that either partially or simultaneously there are: 1). There is a direct relationship between employee potential (X1) and Employee Performance (Y) with a correlation coefficient of 0.73. 2) a direct relationship between employee competence (X2) and employee performance (Y) with a correlation coefficient of 0.83. 3) a direct relationship between work motivation (X3) and employee performance (Y) with a correlation coefficient of 0.53. 4) there is a simultaneous direct relationship between employee potential (X1), employee competence (X2), and work motivation (X3) with employee performance (Y) , with an Fcount of 68.89 and Ftable of 4.01 with a correlation coefficient (Rx1x2x3Y ) of 0.883. The implication of this research is that based on the results of the analysis, it is known that from the two structural models studied, in the first model, namely employee performance as an endogenous variable, competence is the dominant factor that affects employee performance when compared to work motivation. In structural model 2 which places employee potential as an endogenous variable, it is known that employee performance is the dominant factor, then competence and finally work motivation. Based on these findings, the priority of improving employee performance can be done through increasing potential, employee competence and work motivation.